Louise Trapeze is totally 100% fearless - Ostow, Micol (Ostow, Micol. Louise Trapeze, 2015)
"Six-year-old Louise Trapeze lives at the circus and can't wait to fly on the trapeze until she discovers that she is afraid of heights"--